Effect of Muscle Fatigue on EMG Signal and Maximum Heart Rate for Pre and Post Physical Activity - Endro Yulianto; Arifah Putri Caesaria; Sari Luthfiyah; Triwiyanto Triwiyanto; Achmad Rizal (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2023)
Sport is a physical activity that can optimize body development through muscle movement. Physical activity without rest with strong and prolonged muscle contractions results in muscle fatigue. Muscle fatigue that occurs causes a decrease in the work efficiency of muscles. Electrocardiography (ECG) is a recording of the heart's electrical activity on the body's surface. EMG is a technique for measuring electrical activity in muscles. This study aims to detect the effect of muscle fatigue on cardiac signals by monitoring ECG and EMG signals. This research method uses the Maximum Heart Rate with a research design of one group pre-test-post-test. The independent variable is the ECG signal when doing plank activities, while the dependent variable is the result of monitoring the ECG signal. To get the Maximum Heart Rate results, respondents use the Karnoven formula and perform the T-test. Test results show a significant value (pValue <0.05) in pre-exercise and post-exercise. When the respondent experiences muscle fatigue, it shows the effect of changes in the shape of the ECG signal which is marked by the presence of movement artifact noise. It concluded that the tools in this study can be used properly. This study has limitations including noise in the AD8232 module circuit and the display on telemetry where the width of the box cannot be adjusted according to the ECG paper.is It recommended for further research to use components with better quality and replace the display using the Delphi interface.